Orientación del rol sexual en mujeres que trabajan en profesiones sexualmente tipificadas - Baruch Goldstein, Miriam (1991)
Two hundred eighty-eight Peruvian women from traditionally masculine and feminine professions were compared on their global, family and work sex role orientation (Raguz' SROS, 1989). Analysis of variance and t-tests showed significant differences in sex role orientation only in the work context. Results are discussed.